SMARTPHONE NATIVES, COMPUTER LEARNERS: TENSIONS IN BUILDING DIGITAL AUTONOMY IN A SCHOOL CONTEXT - da Cunha Santiago, Izael; Aparecida Guerino Ragonezi, Helaing; Luciene Rocha Gomes, Martha (Revista Gênero e Interdisciplinaridade, 2026)
This article examines the tensions between high levels of youth digital connectivity and the effective development of technological autonomy in school contexts. The study was conducted with first-year high school students during pedagogical activities in a computer laboratory at a public school, adopting a qualitative observational approach. Empirical records revealed difficulties related to basic operational procedures, digital file organization, and the adaptation of technology-mediated writing to academic requirements, indicating a gap between everyday use of mobile devices and functional computer skills in school practices. The findings also showed the transfer of communication patterns typical of smartphone interactions into academic textual production, as well as a reliance on technological automatisms that may constrain the development of students’ digital autonomy. In dialogue with theoretical perspectives on digital culture and schooling, the study proposes the concept of the digital autonomy paradox as an analytical category to problematize the frequently assumed notion of youth technological competence in educational discourse. It is concluded that the construction of digital autonomy requires intentional and systematic learning experiences capable of articulating informal digital practices with the cognitive and academic demands of basic education.